La musique et le mal : possession diabolique dans Trilby (1894) de George du Maurier et The Lost Stradivarius (1895) de John Falkner Meade - Françoise Dupeyron-Lafay (Cahiers Victoriens et Edouardiens)
These two fin-de-siècle fantastic novels present music (opera-singing in Trilby and violin-playing in The Lost Stradivarius) as a supernatural agent enabling the singer or player to get access to a superhuman status and transcendental dimension. However, the function of music in these books is utterly negative : it is of foreign origin — this reflects some Anglo-saxon xenophobic prejudices ; Svengali is an East European Jew in Trilby and Falkner Meade makes southern Italy instrumental in his plot — which certainly accounts for its being evil. In the two books, the protagonists are possessed and enslaved by music which, like a vampire, exhausts them and drains them empty, dissolves their identity and robs them of their willpower. The diabolic possession at work is also, more or less explicitly, of an erotic nature — in both cases, a male character holds a victim in bondage through music — but the inevitable outcome is death.